The Impact of Teacher Attitude and Mobile Technology on Student Engagement - Natalie Anjelly; Rivalyn Cinthia Putry; Ananda Fortunisa (Universitas Darussalam Gontor, 2024)
This research investigates the influence of teacher attitudes and mobile technology interaction on student engagement in the classroom. Student engagement refers to the level of interest, motivation, and commitment thatstudents demonstrate towards their learning and involvement in the educational process. Teacher attitudes refer to the beliefs, perceptions and dispositions that educators hold towards their profession, their students and the educationalprocess. Mobile technology is technology that can be taken wherever the user goes. Using a quantitative approach, data is collected from samples of students who are currently studying or who have graduated through surveys, classobservations and additional interviews. Because this research topic has never been conducted before, the researcher is interested in discussing